Intelligence in early adulthood and subsequent risk of unintentional injury over two decades: cohort study of 1 109 475 Swedish men. Issue 5 (1st December 2009) - Whitley, E; Batty, G D; Gale, C R; Deary, I J; Tynelius, P; Rasmussen, F
Abstract : Background: There is growing evidence of an inverse association between intelligence (IQ) and unintentional injuries. Methods: Analyses are based on a cohort of 1 109 475 Swedish men with IQ measured in early adulthood. Men were followed up for an average 24 years, and hospital admissions for unintentional injury were recorded. Results: 198 133 (17.9%) men had at least one hospital admission for any unintentional injury during follow-up. The most common cause of unintentional injury was falling, followed by road accidents, poisoning, fire and drowning. In addition, 14 637 (1.3%) men had at least one admission for complications of medical care. After adjusting for confounding variables, lower IQ scores were associated with an elevated risk of any unintentional injury (HR (95% CI) per SD decrease in IQ: 1.15 (1.14 to 1.15)) and of cause-specific injuries other than drowning (poisoning (1.53 (1.49 to 1.57)), fire (1.36 (1.31 to 1.41)), road traffic accidents (1.25 (1.23 to 1.26)), medical complications (1.20 (1.18 to 1.22)) and falling (1.17 (1.16 to 1.18))). These gradients were stepwise across the full IQ range. Conclusions: Low IQ scores in early adulthood were associated with a subsequently increased risk of unintentional injury. A greater understanding of mechanisms underlying these associations may provide opportunities and strategies for prevention.